Economics of Ukraine’s biodiversity - Koretskyi, Mykola; Yakymchuk, Alina; Корецький, М. Х.; Якимчук, А. Ю. (Харківський національний автомобільно-дорожній університет, 2015)
In the article the analysis of economical state and local management systems of the Ukrainian biodiversity has been done. The biodiversity conservation functions analysis and classification have been carried out. The economic effect of biodiversity functioning has been estimated using forests and swamps ecosystems as an example. The necessity of biodiversity in the GDP of the state has been justified. The study of the concept of sustainable development as the most promising in terms of biodiversity has been investigated. The main methods and tools of biodiversity conservation, the best practices of biodiversity conservation have been learned. The basic measures improving governance biodiversity of Ukraine in accordance with the concept of sustainable development have been ordered. The study was conducted on the basis of a systematic method. Scientific and practical interest in the work is the proposed funding mechanism for biodiversity conservation in the current economic climate of Ukraine. The organizational structure of government biodiversity conservation of Ukraine has been investigated. The effectiveness of government biodiversity conservation has been investigated. The functions of the Ministry of Ecology and Natural Resources of Ukraine as a central body of executive power in the field of biodiversity conservation have been studied and analyzed. The best foreign practices of biodiversity conservation and recommendations for its implementation in Ukraine have been ordered.
Економіка біорізноманіття України
Keywords: ecosystems; biodiversity; conservation; economic; екосистеми; біорізноманіття; збереження; економіка; 351:354